2013
DOI: 10.1155/2013/369345
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Scalpel versus Conventional Haemostasis in Neck Dissection: A Prospective Randomized Study

Abstract: Purpose. The aim of this prospective randomized trial was to compare operative factors, postoperative outcomes, and surgical complications of neck dissection (ND) when using the harmonic scalpel (HS) versus conventional haemostasis (CH) (classic technique of tying and knots, resorbable ligature, and bipolar diathermy). Materials and methods. Sixty-one patients who underwent ND with primary head and neck cancer (HNSCC) resection were enrolled in this study and were randomized into two homogeneous groups: CH (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…The studies by Dean [ 11 ] and Salami et al [ 16 ] were identified as being of a lower design quality because neither comprised blinded participants or an outcome assessment, and the use and reporting of random sequence generation and allocation concealment may have been inadequate. In addition, the quality of the studies by Ferri [ 8 ] and Walen et al [ 14 ] was moderate ( Fig 2 ). Overall, the agreement between the two assessors about the quality of the seven studies was moderate or high, although there was still some controversy.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The studies by Dean [ 11 ] and Salami et al [ 16 ] were identified as being of a lower design quality because neither comprised blinded participants or an outcome assessment, and the use and reporting of random sequence generation and allocation concealment may have been inadequate. In addition, the quality of the studies by Ferri [ 8 ] and Walen et al [ 14 ] was moderate ( Fig 2 ). Overall, the agreement between the two assessors about the quality of the seven studies was moderate or high, although there was still some controversy.…”
Section: Resultsmentioning
confidence: 98%
“…When the six studies were quantitatively combined, the mean difference in the total drainage fluid volume for the neck dissection was 64.9 milliliters less using the harmonic scalpel compared with conventional hemostasis [mean difference: -64.86; 95% CI = (-110.40, -19.32); P = 0.005] ( Fig 7 ). However, the statistical heterogeneity was great and was driven by three studies (Ferri [ 8 ], Dean [ 11 ] and Miccoli et al [ 15 ]). When these three studies were excluded, the heterogeneity and the effect measure were not significant [I 2 = 0%; mean difference: 3.09; 95% CI = (-7.99, 14.17); P = 0.58] ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Studies claim the benefits of this equipment, including allowing faster and safe surgical procedures. 29 However, the alerts show that no device is exempt from technical and human failures; for example, there might be improper cutting.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative hemorrhage includes hematoma formation, jugular vein rupture, and carotid blowout. Hematomas are reported to have an incidence of 2% in oral cancer surgery and account for most of the hemorrhage cases . Jugular vein ruptures may result from infections or iatrogenic vessel wall injuries .…”
Section: Discussionmentioning
confidence: 99%